2023
DOI: 10.3390/jcm12072612
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Technological Rehabilitation in Patients with Intensive Care Unit Weakness: A Randomized Controlled Pilot Study

Abstract: Intensive-Care-Unit-Acquired Weakness (ICU-AW) is the most common neuromuscular impairment in critically ill patients and can have a significant impact on long-term disability. Early rehabilitation has been suggested to facilitate the natural recovery process. This is a pilot, randomized, single-blind study that aimed to evaluate the effectiveness of intensive combined technological rehabilitation treatment including focal muscle vibration and non-immersive virtual reality for patients with severe acquired bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Investigating users' perceptions of neurorehabilitation is pivotal, as patients' motivation significantly predicts long-term changes in quality of life and rehabilitation outcomes [7]. Previous research confirmed that the combined use of conventional methods and technological devices could maximize rehabilitation effectiveness [60,[62][63][64]. Furthermore, our findings highlighted the satisfaction of patients with the multidisciplinary rehabilitation treatment and their active involvement in the recovery process.…”
Section: Motivation Patient Satisfaction Quality Of Lifesupporting
confidence: 59%
“…Investigating users' perceptions of neurorehabilitation is pivotal, as patients' motivation significantly predicts long-term changes in quality of life and rehabilitation outcomes [7]. Previous research confirmed that the combined use of conventional methods and technological devices could maximize rehabilitation effectiveness [60,[62][63][64]. Furthermore, our findings highlighted the satisfaction of patients with the multidisciplinary rehabilitation treatment and their active involvement in the recovery process.…”
Section: Motivation Patient Satisfaction Quality Of Lifesupporting
confidence: 59%
“…The use of VR in the neurorehabilitation field has been increasing in the ten last years, demonstrating its efficacy in promoting cognitive [40] as well as motor recovery [41]. Kober et al, 2013 [42] suggested that the VR technique creates natural, customized, and complex simulated environments in which spatial deficits, such as disorientation and the ability to locate landmarks, can be examined in an accurate and ecologically sound manner.…”
Section: Discussionmentioning
confidence: 99%
“…Novel VR-based technologies are constantly developing, and their areas of application are expanding and even overlapping, as we see in neuroscience. Table 1 presents and indicates examples of neuroscientific areas of using virtual environments and tools, including pain management [31,[56][57][58], improvement of brain injury patients [5,26,[59][60][61], post-stroke [10,20,25,33,[65][66][67], prevention, and diagnosis and therapy of many serious illnesses. Examples include diseases such as neurodevelopmental disorders (e.g., attentiondeficit hyperactivity disorder, ADHD [22,80,81]); schizophrenia spectrum disorders (e.g., schizophrenia [82,83]); autism spectrum disorders (e.g., autism [84,85]); mood (e.g., depressive disorders [86,87]), anxiety (e.g., panic and phobias [74][75][76]), trauma-and stressorrelated (e.g., post-traumatic stress disorder, PTSD [73]), neurocognitive (e.g., Parkinson's or Alzheimer's and memory cognitive impairment diseases [23,24,47,[69][70][71][72][77][78][79]) and neuromuscular disorders (e.g., multiple sclerosis [32,…”
Section: Hinze Et Al 2021 [76]mentioning
confidence: 99%
“…Although unusual and unexpected challenges are only beginning to be encountered, VR environments make it possible to expand the scope of research on perception, cognitive and motor imagery, and the effects of different learning and teaching pathways. In this context, studies of neuroplasticity phenomena, including the effects of applied virtual (mirror) tasks and training, are of interest in virtual prevention, neurogeriatrics, neurotherapy and neurorehabilitation [5,[31][32][33]36,42,58,61].…”
Section: Hinze Et Al 2021 [76]mentioning
confidence: 99%